1999
DOI: 10.1098/rstb.1999.0441
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of neuromuscular control in lamprey swimming

Abstract: The neuronal generation of vertebrate locomotion has been extensively studied in the lamprey. Models at di¡erent levels of abstraction are being used to describe this system, from abstract nonlinear oscillators to interconnected model neurons comprising multiple compartments and a Hodgkin^Huxley representation of the most relevant ion channels. To study the role of sensory feedback by simulation, it eventually also becomes necessary to incorporate the mechanical movements in the models. By using simplifying mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 36 publications
0
72
2
Order By: Relevance
“…Because of the high complexity, mathematical modeling is essential for understanding mechanisms underlying neuronal information processing in the CNS. Taking animal locomotion as a tractable focus of study, a number of models have previously been developed, ranging from neuronal circuit models for CPGs (44)(45)(46)(47) and body-fluid interactions during swimming (35,48) to integrated neuromechanical models for locomotion (49)(50)(51). An ultimate goal is to have dynamical models that are simple and amenable not only to numerical simulations but also to analytical studies, and which are fully validated by experimental data, with demonstrated predictability under perturbed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high complexity, mathematical modeling is essential for understanding mechanisms underlying neuronal information processing in the CNS. Taking animal locomotion as a tractable focus of study, a number of models have previously been developed, ranging from neuronal circuit models for CPGs (44)(45)(46)(47) and body-fluid interactions during swimming (35,48) to integrated neuromechanical models for locomotion (49)(50)(51). An ultimate goal is to have dynamical models that are simple and amenable not only to numerical simulations but also to analytical studies, and which are fully validated by experimental data, with demonstrated predictability under perturbed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Each CPG spinal region exhibits its own oscillatory frequency, but could entrain the rostral or/and caudal segments, respectively. Work on the lamprey has elucidated the structure and function of CPGs and the rostrocaudal gradient of excitation and led to impressive computer simulations (Ekeberg & Grillner 1999). Although the real neuronal circuit of a CPG has not yet been demonstrated in the limbed vertebrates (tetrapods), Ijspeert (2001) has succeeded to simulate a salamander during undulation and legged locomotion, thus the hypothetical basis for action of CPGs during legged locomotion has become more clear (http://lslwww.epfl.ch/birg).…”
Section: Control Of the Vertebrate Motion Systems (A ) Central Pattermentioning
confidence: 99%
“…The hydrodynamics of swimming has been the subject of a variety of studies for more than half a century from experimental (3-6), theoretical (7)(8)(9)(10)(11), and computational (12)(13)(14)(15)(16)(17)(18)(19) perspectives. Recently there has been growing interest in integrating these physical approaches with neurobiological models using coupled neuromechanical simulations (20) and biomimetic devices (21,22) to study developmental and evolutionary aspects of the problem. Indeed, when a dead fish is dragged through water it flutters and moves in a manner reminiscent of a live, swimming fish (23).…”
mentioning
confidence: 99%